Религиозный ренессанс: попытка социологической диагностики - Рязанова, Л. (Социология: теория, методы, маркетинг, 2001)
The last decade of the 20th century revealed a rise in religious beliefs in Ukrainian society. Analyzing the religious social and historical context, the author stresses influence of the social trauma, like anomie, crisis of identity and legitimacy, civilization incompetence. Special attention is paid to secularization and post-modern culture effects on religious actualization. Sociological data prove the fact of religious renaissance although they reveal cognitive dissonance in consciousness of believers,weak interiorization of religious values, their religious incompetence. Therefore we cannot expect that any rise in religious beliefs will be sufficient for overcoming crisis and its consequences.